Acurácia dos indicadores clínicos do diagnóstico de enfermagem disfunção sexual em mulheres com câncer de mama em tratamento farmacológico - Ferreira, Iarlla Silva (2018)
Sexual well-being is one of the impaired domains in the quality of life of women diagnosed with breast neoplasm and it is directly affected by the impact of the diagnosis and the adverse effects of the therapeutic modalities. Thus, women with breast cancer need diagnoses and interventions directly aimed at their needs. The objective of this study is to analyze the accuracy measures of the clinical indicators of the nursing diagnosis "Sexual Dysfunction" in women with breast cancer under pharmacological treatment. The researchers developed a study of the accuracy of clinical indicators (defining characteristics) concerning this nursing diagnosis using a consecutive non-probabilistic sampling. This research design aims to measure how much a clinical indicator is useful to determine the presence or not of a diagnosis. The study was conducted at the chemotherapy outpatient clinic of two reference hospitals in the state of Ceará, located in the city of Fortaleza, with a sample of 120 patients undergoing pharmacological treatment with chemotherapy, hormonal therapy or biological therapy. The data were collected from May to October 2017 with an instrument constructed based on the defining characteristics of the said diagnosis and on clinical indicators identified in an integrative review, as well as sociodemographic and clinical data. To verify the sensitivity, specificity and predictive values (positive and negative) of each indicator, the Latent Class Analysis method was used. The incidence of Sexual Dysfunction in women who participated in the study was 80.8%. The clinical indicator with the highest sensitivity was the reduction in sexual desire (75%), while undesirable change in sexual function (specificity = 96%, positive predictive value = 98%), orgasm change (specificity = 96%, positive predictive value = 98% ), change in sexual role (specificity = 91%, positive predictive value = 94%), reduction of sexual desire (specificity = 91%, positive predictive value = 97%) and vaginismus (specificity = 91%, positive predictive value = 95%) were the clinical indicators with greater specificity. It is concluded that the present study allowed the measurement of the clinical indicators accuracy of Sexual Dysfunction in women with breast cancer undergoing pharmacological treatment with chemotherapy, hormonal therapy or biological therapy. The results of this study may contribute to a better understanding of its manifestation, to diagnose it early, to identify the most frequent and the most accurate signs and symptoms, as well as to confirm this diagnosis.